2020
DOI: 10.1002/lno.11445
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and isotopic composition of mercury in a blackwater river affected by extreme flooding events

Abstract: Torrential rain and extreme flooding caused by Atlantic hurricanes mobilize a large pool of organic matter (OM) from coastal forested watersheds in the southeastern United States. However, the mobilization of toxic metals such as mercury (Hg) that are associated with this vast pool of OM are rarely measured. This study aims to assess the variations of total Hg (THg) and methylmercury (MeHg) levels and the isotopic compositions of Hg in a blackwater river (Waccamaw River, SC, U.S.A.) during two recent extreme f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
(68 reference statements)
2
10
0
Order By: Relevance
“…This can be attributed to the difficulty in collecting enough biomass and amount of Hg to perform high-precision Hg isotope analysis. 147 Further, the highly variable fraction of MeHg present as total Hg (%MeHg between 0.7 and 100% in forest floor food webs 146 ) makes it difficult to interpret the Hg isotope data of total Hg because the isotope ratios of iHg and MeHg could be drastically different even in a single region or ecosystem. For example, in a study on stream and forest food webs in a northern California watershed, Tsui et al (2012) 42 demonstrated that %MeHg is significantly correlated with δ 202 Hg and Δ 199 Hg in each food web.…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the difficulty in collecting enough biomass and amount of Hg to perform high-precision Hg isotope analysis. 147 Further, the highly variable fraction of MeHg present as total Hg (%MeHg between 0.7 and 100% in forest floor food webs 146 ) makes it difficult to interpret the Hg isotope data of total Hg because the isotope ratios of iHg and MeHg could be drastically different even in a single region or ecosystem. For example, in a study on stream and forest food webs in a northern California watershed, Tsui et al (2012) 42 demonstrated that %MeHg is significantly correlated with δ 202 Hg and Δ 199 Hg in each food web.…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“…Similar to phytoplankton, measurements of Hg isotope ratios and the fractionation occurring in invertebrates are not widely studied in comparison to animal consumers of higher trophic levels. This can be attributed to the difficulty in collecting enough biomass and amount of Hg to perform high-precision Hg isotope analysis . Further, the highly variable fraction of MeHg present as total Hg (%MeHg between 0.7 and 100% in forest floor food webs) makes it difficult to interpret the Hg isotope data of total Hg because the isotope ratios of iHg and MeHg could be drastically different even in a single region or ecosystem.…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“…In addition, DOC can form extremely strong complexes with metals, not only enhancing metal solubility and mobility but also affecting its bioavailability and toxicity (Aiken et al., 2011; Baken et al., 2011). For example, strong correlations between total mercury and DOC concentrations were reported worldwide, including in blackwater streams in the southeastern United States (Tsui et al., 2020), runoff after wildfires in California (Ku et al., 2018), and other ecosystems (Ravichandran, 2004). Uptake of metals by aquatic organisms can also depend on the characteristics of DOC (Baken et al., 2011).…”
Section: Functional Variability In Doc Along the Water Continuummentioning
confidence: 99%
“…Carbon stable isotope values (δ 13 C) change very little through trophic linkages and act as indices of foraging behavior and fish habitat . Stable isotope values of nitrogen (δ 15 N) undergo predictable trophic enrichment from prey to predators, allowing us to estimate trophic position. , While information regarding MeHg bioaccumulation and biomagnification can be inferred from δ 13 C and δ 15 N analyses, the connection of Hg sources through dietary pathways is best assessed by including Hg stable isotope analyses. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…12,13 While information regarding MeHg bioaccumulation and biomagnification can be inferred from δ 13 C and δ 15 N analyses, the connection of Hg sources through dietary pathways is best assessed by including Hg stable isotope analyses. 1,12,14,15 Combining δ 13 C and δ 15 N with Hg stable isotope values facilitates determination of Hg sources and energy pathways to fish, but less commonly tested is the connection between fish habitat use and Hg sources in ecosystems where heterogeneity of Hg sources exists. 12 Mass-dependent fractionation (MDF) of Hg isotopes (represented as δ 202 Hg) enables inferences about Hg sources 16−18 and reaction processes.…”
Section: ■ Introductionmentioning
confidence: 99%